THE GENESIS OF THE PRINCIPLES OF THE LEGAL STATUS OF AN INDIVIDUAL IN EUROPEAN INTERNATIONAL LEGAL REALITY - Tetiana Psota (Вісник Харківського національного університету імені В. Н. Каразіна Серія: «Право»)
Introduction. The article considers historical and legal origins of the foundations of the legal status of an individual in the European system of protection of human rights and freedoms as part of international legal reality of the region. The work examines the phenomenon of the legal status of a person in the European international legal reality in view of its modern normative regulation, protection mechanisms at the regional level and worldview sources of the evolution of its foundations.